An Assessment of the Intercultural Communicative Competence of Kurdish EFL University Students: A Linguacultural Study - Hassan, Zana Mahmood (Sulaimani Journal for Humanities, 2019)
It is widely accepted that language and culture are intertwined. Language and cultural awareness are so integrated that a successful communication requires linguistic and cultural competence. This requirement becomes vital in the case of foreign language learning. Learning languages do not equip learners just with linguistic abilities, but their cultural awareness could be affected in many ways. Even with adequate linguistics abilities, whether cultural barriers prevent a successful communication remains a question that needs investigation. Enhancing cultural awareness, along with linguistic competence, is crucial for communication. This paper assesses the intercultural communicative competence of Kurdish EFL university students who will be specialized in English language and literature. To this end, a questionnaire of fourteen major questions with three follow up questions has been utilized to collect data from 150 Journal of Zankoy Sulaimani-Part B / for Humanities No (60) (1 May 2019) 36١ EFL learners from three major universities in the region. The questions are based on Byram’s (1997) model of knowledge, skill and behaviour to assess intercultural competence. This paper hypothesizes that Kurdish EFL learners’ cultural awareness of the target culture in terms of social cognition, self-awareness and behaviour has been affected to a large extent due to learning English. To validate or refute this claim, after discussing the results, some conclusions are drawn.
Keywords: الكفاءة اللغوية والثقافية بين الثقافات; متحدث متعدد الثقافات; متعلمو اللغة الإنجليزية كلغة أجنبية